P‐20: Image Distortion and Image Correction of Curved OLED Displays. Issue 1 (25th September 2020) - Lee, Wei-Kai; Chen, Po-Jui; Cyue, Zih-Rou; Wu, Chung-Chih
Abstract : Although flexible and curved OLED displays can bring many novel and interesting applications, their curved structure would also impact optical and image characteristics critical for displays. Here we perform quantitative analyses on geometric distortion and brightness reduction induced by the curved shape and then propose the effective image correction method to re‐construct a proper image for curved OLED displays.